Default options in advance directives: study protocol for a randomised clinical trial. Issue 6 (6th June 2016) - Gabler, Nicole B; Cooney, Elizabeth; Small, Dylan S; Troxel, Andrea B; Arnold, Robert M; White, Douglas B; Angus, Derek C; Loewenstein, George; Volpp, Kevin G; Bryce, Cindy L; Halpern, Scott D
Abstract : Introduction: Although most seriously ill Americans wish to avoid burdensome and aggressive care at the end of life, such care is often provided unless patients or family members specifically request otherwise. Advance directives (ADs) were created to provide opportunities to set limits on aggressive care near life's end. This study tests the hypothesis that redesigning ADs such that comfort-oriented care is provided as the default, rather than requiring patients to actively choose it, will promote better patient-centred outcomes. Methods and analysis: This multicentre trial randomises seriously ill adults to receive 1 of 3 different ADs: (1) a traditional AD that requires patients to actively choose their goals of care or preferences for specific interventions (eg, feeding tube insertion) or otherwise have their care guided by their surrogates and the prevailing societal default toward aggressive care; (2) an AD that defaults to life-extending care and receipt of life-sustaining interventions, enabling patients to opt out from such care; or (3) an AD that defaults to comfort care, enabling patients to opt into life-extending care. We seek to enrol 270 patients who return complete, legally valid ADs so as to generate sufficient power to detect differences in the primary outcome of hospital-free days (days alive and not in an acute care facility). Secondary outcomes include hospital and intensive care unit admissions, costs of care, hospice usage, decision conflict and satisfaction, quality of life, concordance of preferences with care received and bereavement outcomes for surrogates of patients who die. Ethics and dissemination: This study has been approved by the Institutional Review Boards at all trial centres, and is guided by a data safety and monitoring board and an ethics advisory board. Study results will be disseminated using methods that describe the results in ways that key stakeholders can best understand and implement. Trial registration number: NCT02017548; Pre-results.